Psoriasis and risk of celiac disease: A systematic review and meta-analysis - Patompong Ungprasert; Karn Wijarnpreecha; Wonngarm Kittanamongkolchai (Wolters Kluwer Medknow Publications, 2017)
Background and Objectives: The possible association between psoriasis and celiac disease (CD) has long been observed, but epidemiologic studies attempting to characterize this association have yielded inconclusive results. This meta-analysis was conducted with the aims to summarize all available data. Methods: We conducted a systematic review and meta-analysis of observational studies that reported relative risk, hazard ratio, odds ratio (OR), or standardized incidence ratio with 95% confidence interval (CI) comparing the risk of CD in patients with psoriasis versus participants without psoriasis. Pooled risk ratio and 95% CI were calculated using random-effect, generic inverse-variance methods of DerSimonian and Laird. Results: Four retrospective cohort studies with 12,912 cases of psoriasis and 24,739 comparators were included in this meta-analysis. The pooled analysis demonstrated a significantly higher risk of CD among patients with psoriasis compared with participants without psoriasis with the pooled OR of 3.09 (95% CI, 1.92-4.97). Limitations: Most primary studies reported unadjusted estimated effect, raising a concern over confounders. Conclusions: Our meta-analysis demonstrated an approximately 3-fold increased risk of CD among patients with psoriasis.